Artemisinin resistance in Plasmodium falciparum is associated with an altered temporal pattern of transcription. - Mok, S; Imwong, M; Mackinnon, M; Sim, J; Ramadoss, R; Yi, P; Mayxay, M; Chotivanich, K; Liong, K; Russell, B; Socheat, D; Newton, P; et al. (BioMed Central, 2011)
BACKGROUND: Artemisinin resistance in Plasmodium falciparum malaria has emerged in Western Cambodia. This is a major threat to global plans to control and eliminate malaria as the artemisinins are a key component of antimalarial treatment throughout the world. To identify key features associated with the delayed parasite clearance phenotype, we employed DNA microarrays to profile the physiological gene expression pattern of the resistant isolates. RESULTS: In the ring and trophozoite stages, we observed reduced expression of many basic metabolic and cellular pathways which suggests a slower growth and maturation of these parasites during the first half of the asexual intraerythrocytic developmental cycle (IDC). In the schizont stage, there is an increased expression of essentially all functionalities associated with protein metabolism which indicates the prolonged and thus increased capacity of protein synthesis during the second half of the resistant parasite IDC. This modulation of the P. falciparum intraerythrocytic transcriptome may result from differential expression of regulatory proteins such as transcription factors or chromatin remodeling associated proteins. In addition, there is a unique and uniform copy number variation pattern in the Cambodian parasites which may represent an underlying genetic background that contributes to the resistance phenotype. CONCLUSIONS: The decreased metabolic activities in the ring stages are consistent with previous suggestions of higher resilience of the early developmental stages to artemisinin. Moreover, the increased capacity of protein synthesis and protein turnover in the schizont stage may contribute to artemisinin resistance by counteracting the protein damage caused by the oxidative stress and/or protein alkylation effect of this drug. This study reports the first global transcriptional survey of artemisinin resistant parasites and provides insight to the complexities of the molecular basis of pathogens with drug resistance phenotypes in vivo.